SEISMOACOUSTIC MONITORING OF THE STATE OF THE SOILS OF THE DNIESTRIAN SLOPE (IN THE ZONE OF ACCOMMODATION OF THE PRESSURE-STATIONARY UNIT) - Deineko, S.; Vyzhva, S.; Nesterenko, G.; Bernevek, A.; Ivaschenko, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The Dniester hydroelectric power station, like most HPPs, is built in complex structural-tectonic and engineering-geological conditions. The condition of structures located on a steep slope is affected by man-made (shaking of the territory when discharging water) and natural (large amount of precipitation contributes to the intensification of landslide processes) factors. To monitor the state of safety of the "soil-construction" system, seismoacoustic monitoring was started. The article presents the results of seismoacoustic studies of stationary wells on the Dniester slope. Initial characteristics of the speed of propagation of elastic waves in rocks of the geological section of the study area were received. The results of the measurements of 2016 serve as basic ones, in order to compare with the results of measurements of the following years in order to identify possible changes in the state of soils, and, if necessary, to take the necessary measures to strengthen the slope.
Keywords: soil; hydraulic engineering structure; monitoring; seism acoustic research; cross-hole seismic testing; seismic tomography